Immunomodulatory role of RNA modifications in sex hormone-dependent cancers - Jiang, Yujia; Liang, Xiaolan; Sun, Hongyi; Yin, Ping; Zhou, Jing; Yu, Chaoqin (Frontiers in Immunology, 2025)
Recent studies have identified that RNA epigenetic modifications, including m6A, m1A, m5C, etc, play pivotal roles in tumor progression. These modifications influence mRNA stability, RNA processing, translational efficiency, and decoding precision. However, comprehensive reviews detailing the connection between m6A RNA modifications and hormone-dependent cancers in both male and female populations remain scarce(breast cancer, ovarian cancer, and endometrial cancer, prostate cancer). In this article, we explore the cellular and molecular roles of various RNA modifications alongside the key elements of the tumor microenvironment. We examine how these RNA modifications influence the development of hormone-dependent cancers through their impact on immune mechanisms. By enhancing our understanding of the function of RNA modifications within the immune systems of four specific tumors, we offer fresh insights for their potential applications in diagnosis and treatment.